Problems with the electronic health record - de Ruiter, Hans-Peter (Nursing philosophy, 2016)
One of the most significant changes in modern healthcare delivery has been the evolution of the paper record to the electronic health record (EHR). In this paper we argue that the primary change has been a shift in the focus of documentation from monitoring individual patient progress to recording data pertinent to Institutional Priorities (IPs). The specific IPs to which we refer include: finance/reimbursement; risk management/legal considerations; quality improvement/safety initiatives; meeting regulatory and accreditation standards; and patient care delivery/evidence based practice. Following a brief history of the transition from the paper record to the EHR, the authors discuss unintended or contested consequences resulting from this change. These changes primarily reflect changes in the organization and amount of clinician work and clinician-patient relationships. The paper is not a research report but was informed by an institutional ethnography the aim of which was to understand how the EHR impacted clinicians and administrators in a large, urban hospital in the United States. The paper was also informed by other sources, including the philosophies of Jacques Ellul, Don Idhe, and Langdon Winner.